The Effect of Weed Control with Pre-Emergence Herbicides on the Yield Level of Mung Bean Yield - Cailing Jing; Junying Wang; Yonghong Wu; Yufan Zhou; Huijun Zhu; Yaowen Zhang; Shuqi Dong; Xiaorui Li; Juan Zhao; Junli Cao; Xiangyang Yuan; Xi’e Song (Plants)
The mung bean (Vigna radiata (Linn) Wilczek.) is a major grain crop in China, but its yield is significantly impacted by weeds. However, no pre-emergence herbicides are registered for mung bean fields in the China Pesticide Information Network. Screening for efficient and safe pre-emergence herbicides could improve mung bean production efficiency. In this study, six pre-emergence herbicides were selected: 480 g/L alachlor (1935.00 g a.i ha−1), 720 g/L metolachlor (1620.00 g a.i ha−1), 100 g/L imazethapyr (100.50 g a.i ha−1), 338 g/L oxadiazon (507.00 g a.i ha−1), 330 g/L pendimethalin (144.00 g a.i ha−1), and 480 g/L trifluralin (720.00 g a.i ha−1). Through Petri dish screening, a spraying treatment was carried out before seed germination. By measuring the root length and shoot length, imazethapyr (100.50 g a.i ha−1) and oxadiazon (507.00 g a.i ha−1) were screened out. They were applied to potted plants and sprayed after sowing. The results showed that imazethapyr (100.50 g a.i. ha−1) and oxadiazon (507.00 g a.i. ha−1) had no inhibitory effect on the growth and development of the mung bean. Subsequently, experiments were conducted with imazethapyr (100.50 g a.i ha−1) and oxadiazon (507.00 g a.i ha−1) applied in the field. Compared to the control, under imazethapyr (100.50 g a.i ha−1) and oxadiazon (507.00 g a.i ha−1), the agronomic traits, photosynthetic pigment content, yield, and yield components were not inhibited; the activities of superoxide dismutase, peroxidase, and catalase were increased; and gas exchange and chlorophyll fluorescence were not inhibited. In addition, soil urease activity decreased and soil invertase and alkaline phosphatase activity increased after 60 d of treatment. In summary, imazethapyr and oxadiazon can effectively control weeds and increase mung bean yield. The purpose of this study is to screen out safe and efficient pre-emergence herbicides suitable for the Shanxi mung bean, which is of great significance due to its large-scale planting industrialization and the development of advantageous industries.